In-Vitro cytotoxicity, antibacterial, and UV protection properties of the biosynthesized Zinc oxide nanoparticles for medical textile applications. (December 2018) - Fouda, Amr; EL-Din Hassan, Saad; Salem, Salem S.; Shaheen, Tharwat I.
Abstract: Nowadays, medical textiles have become the most essential and developing part in human healthcare sector. This work was undertaken with a view to harness the bio-active macromolecules secreted by fungi e.g. proteins and enzymes in bio-synthesis of ZnO nanoparticles for multifunctional textiles such as antibacterial activity and UV protection with considering the cytotoxicity limitation. Herein, the isolated fungus, Aspergillus terreus, was allowed to produce proteins which has affinity to cape ZnO-NPs. Various factors affecting the behavior of the secreted proteins on the formed nanoparticles were investigated. Thorough characterizations of the protein capped ZnO-NPs were performed by the using of UV–Visible spectroscopy, transmission electron microscope (TEM) Fourier Transform-Infra Red (FT-IR) spectroscopy, X-ray diffraction (XRD) analysis and Dynamic light scattering analysis (DLS). Prior treatment of cotton fabrics with ZnO-NPs, the cytotoxicity of the protein capped ZnO-NPs was examined. After that, the antibacterial activity of the ZnO-NPs before and after treating of cotton fabrics, besides, the UV-protection (UPF) properties were investigated. Results obviously demonstrated the ability of the bio-secreted protein to cape and reduce ZnO to spherical ZnO-NPs with particle size lied around 10–45 nm, as indicated form UV–vis., spectra TEM, Zeta sizer, FTIR and XRD. Regarding to the results of cytotoxicity, the treatment of the cotton fabrics with ZnO-NPs were performed at safe dose (20 ppm). At this dose, ZnO-NPs loaded samples exhibited reasonable antibacterial activity against both Gram positive and Gram negative bacteria; besides, good UV-protection with reasonable increase in UVA and UVB blocking values. Indeed, nanotechnology based microbiological active molecules opens up new opportunities for us to explore novel applications in terms of green technology. Highlights: Spherical narrow-sized ZnO-NPs were prepared using fungus Aspergillus terreus. Optimization of the biosynthesized ZnO-NPs was performed. Cytotoxicity dose of ZnO-NPs prior application was studied. Antibacterial activity and UV-protection of the treated cotton fabrics were investigated at safe ZnO-NPs dose.